Servqual: strategies to improve university library services - hidayat sutawidjaya, Ahmad; Christina Nawangsari, Lenny (International Journal of Engineering and Technology, 2020)
Over the past two decades, library development in both the functional and physical fields is inseparable from the change in the paradigm of libraries and librarians towards libraries. Increasing competitiveness in university library services is carried out through several aspects; one of which is through the improvement of facilities or infrastructure, products or services produced or personnel responsible for the product to provide customer satisfaction. The purpose of this research is to analysis the attributes of library services and performance of service quality attribute at Wuhan University of China and University of Mercu Buana. The research method used in this study is qualitative and quantitative research with a case study approach and Service Quality method. The population of this study were visitors at the Wuhan University and Mercu Buana University with sample of 100 peoples. As a result of this research libraries of the University of Mercu Buana priority should be given to the improvement are available room, convenience facilities, the availability of the closet, book collection added, Internet services by providing information search/catalogue and appearance of the staff are the dimensions of the material (X1). Reliability variable (X2) is formed with four level indicators expectation was perceived as very high by respondents. The response variable (X3) level expectations is perceived as very high by respondents. Variable reliability (X4), the answers respondents was perceived as very high by respondents. The empathy (X5) variable is very high by respondents, as seen from the responses of the average 4.65 found between a score of 4 (A) and a score of 5 (SA).Â Â